Effects of crop rotation systems on microbial structure under low N application in rice field. (25th February 2020) - Feng, Baohua; Chen, Song; Chu, Guang; Chen, Tingting; Fu, Guanfu; Wang, Danying; Xu, Chunmei; Tao, Longxing; Zhang, Xiufu
Abstract: Crop rotation has been used worldwide for thousands of years. It is well documented that the crop rotation system benefits soil improvement and crop yields. Based on this complexity, the mechanism of benefits still remains elusive. In this study, we used three rotation systems (RW, rice-wheat; RG, rice-green manure crop; and control group RF, rice-fallow) and two N applications (N0: 0 kg Nha −1 and N1: 142.5 kg Nha −1 ) to illustrate the rotation system effects on soil and rice yield under low N application. The obtained results showed that the RW and RG rotation system significantly increased microbial community abundance under N1 application when compared to the RF system, while the RW was more beneficial than the RG system. Furthermore, Acidobacteria showed an advantage in the RW but not in RG under N0 and N1 application, as well as a very close relationship with the pH value, which may be the main reason for the different pH values of these rotation systems.